The impact of halophilic organisms on the grain quality of brine cured hides - (:unkn) unknown (My University, 1996)
Halophilic organisms have long been thought to be associated with reduced grain quality of brine cured cattle hides. However, a direct correlation of the presence of halophiles and damage to surface of the grain has not been previously reported. In this research, a fresh cattle hide was cured in saturated brine to which an innoculum of several isolates of extremely halophilic organisms were added. These halophilic organisms were previously isolated from commercially brine-cured hides. After curing, samples prepared from the hide were stored at three different temperatures, 39°F, 70°F and 106°F. Half of the samples were tanned after four weeks of storage and the remainder of the samples were tanned after seven weeks. Physical testing showed that there was no difference in physical strength between the inoculated and uninoculated samples. Grain damage was observed visually in the samples held for seven weeks at 106°F. Scanning electron micrographs clearly show the nature of this damage.